ANALYZING TEACHER’S INSTRUCTIONAL AND NONVERBAL COMMUNICATION IN EFL CLASSROOM - Ranta, Ranta; Harmawati, Diah (Lingual Journal of Language and Culture; Vol 4 No 2 (2017), 2017)
The objectives of this research were to find out the teacher’s instructional language, kinds of nonverbal communication and effects in EFL Classroom. The objects of the research were the teacher and students of one primary school in Merauke. The approach employed was qualitative approach. The type of this research applied discourse analysis (DA). Data collection was conducted through observation by recording and interview. Data from observa tion was used to know the teacher’s instructional Language and kinds of nonverbal communication. Interview was used to know the effects of using the teacher’s instructional Language and nonverbal communication to the students. The research findings showed that (1) the teacher’s instructional language in the classroom activities covered explanations, asking questions, giving feedback, and giving corrections. In term of explanation, the teacher used English, switched and mixed the Indonesian language. The teacher used display question to know the students understanding related to the material. She used referential question to start the classroom and when she checked the progress of the students’ activity. In giving feedback, mostly same with explanation, the teacher also used English even she switched and mixed her language with Indonesian. The teacher used direct correction and indirect correction in giving correction. Repetition was also found in explanation, asking question, giving feedback and giving correction. (2 that the kind) The findings revealed s of nonverbal communication used by the teacher in the classroom included gesture, body movement and posture, eye contact and facial expression. These nonverbal were applied to explain some unclear verbal communication. (3) The last, the findings showed that there were positive and negative effects of the teacher’s instructional language The positive effects included motivating the students in studying, increasing the students’ vocabulary mastery, making them be more active to speak, giving enthusiasm in studying. Meanwhile, the negative effects revealed the students felt nervous to speak when the teacher looked at them and even she stood beside them. Fundamentally, this research gave great contributions in education, could help student’s confidence and enthusiasm to speak particularly in English learning teaching process. Keywords: Teacher’s instructional, nonverbal communication, EFL